Native and Debranched Rice Starch Modification Using Physical or Chemical Treatment to Increase the Level of Resistant Starch - Wulan, Siti Narsito; Widyaningsih, Tri Dewanti; Kasseri, Dian (Jurnal Teknologi Pertanian, 2007)
Resistant starch, dietary fibres compound, is carbohydrate that escape from human digestion system, therefore it has potential health benefits. A study on resistance starch of the native and debranched starches, obtained from rice, which were further treated with physical or chemical treatment has been conducted. The extracted rice starch was first enzymatic debranched by means of bacterial pullulanase. The debranched starch was then treated further either by autoclaving, extrusion cooking or chemically cross-linking. The native starch was also undergone similar physical or chemical treatments.Â  The results showed that the treated debranched-starch contained a higher level of resistant starch than that of the native starch treated with the similar treatment. The cross linked debranched-starch was the best one and it contained 8.45% moisture, 3.19% ash, 85.44% starch and 3.67% resistant starch. The respective initial gelatinization temperature, gelatinization temperature and maximum viscosity of the modified starch were 79.3oC, 89.6oC and 1478 AU.Key word: resistant starch, enzymatic debranching, physical or chemical modification